2
$\begingroup$

$$\sum_{n=1}^\infty\left(\frac{2n+1}{n^4+2n^3+n^2}\right)=\sum_{n=1}^\infty\left(\frac{2n+1}{n^2}\frac1{{(n+1)}^2}\right)$$ I assume that I should get a telescoping sum in some way, but I'm couldn't find it yet.

$\endgroup$
2
$\begingroup$

Since \begin{align*} \frac{2n+1}{n^4+2n^3+n^2}&=\frac{(n+1)^2-n^2}{n^2(n+1)^2}\\ &=\frac 1{n^2}-\frac 1{(n+1)^2} \end{align*}

then we have, for an integer $N>1$ $$\sum_{n=1}^N\left(\frac{2n+1}{n^4+2n^3+n^2}\right)=1-\frac1{(N+1)^2}$$

$\endgroup$
4
$\begingroup$

Hint: $2n+1=(n+1)^2-n^2$, and telescope.

$\endgroup$
1
$\begingroup$

You'll get a telescoping series, but that is likely just only one of the ingredients for a solution. First, I'll separate the numerator in two parts:

$$ \frac{2n+1}{n^2}\frac{1}{(n+1)^2}=\frac{n+n+1}{n^2(n+1)^2} $$ $$ \frac{2n+1}{n^2}\frac{1}{(n+1)^2}=\frac{1}{n(n+1)^2}+\frac{1}{n^2(n+1)} $$ And of course your telescoping element: $$ \frac{1}{n(n+1)}=\left( \frac{1}{n}-\frac{1}{n+1}\right) $$ Therefore: $$ \frac{2n+1}{n^2}\frac{1}{(n+1)^2}=\frac{1}{n(n+1)}-\frac{1}{(n+1)^2}+\frac{1}{n^2}-\frac{1}{n(n+1)} $$ $$ \frac{2n+1}{n^2}\frac{1}{(n+1)^2}=-\frac{1}{(n+1)^2}+\frac{1}{n^2} $$ And the result is simply 1. As would [WolframAlpha confirm ]( https://www.wolframalpha.com/input/?i=sum((2*n%2B1)%2F((n%5E2(n%2B1)%5E2) )

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.